Cardiac Kir2.1 and NaV1.5 Channels Traffic Together to the Sarcolemma to Control Excitability. Issue 11 (25th May 2018) - Ponce-Balbuena, Daniela; Guerrero-Serna, Guadalupe; Valdivia, Carmen R.; Caballero, Ricardo; Diez-Guerra, F. Javier; Jiménez-Vázquez, Eric N.; Ramírez, Rafael J.; Monteiro da Rocha, André; Herron, Todd J.; Campbell, Katherine F.; Willis, B. Cicero; Alvarado, Francisco J.; et al.
Abstract : Rationale: : In cardiomyocytes, NaV 1.5 and Kir2.1 channels interact dynamically as part of membrane bound macromolecular complexes. Objective: : The objective of this study was to test whether NaV 1.5 and Kir2.1 preassemble during early forward trafficking and travel together to common membrane microdomains. Methods and Results: : In patch-clamp experiments, coexpression of trafficking-deficient mutants Kir2.1 Δ314-315 or Kir2.1 R44A/R46A with wild-type (WT) NaV 1.5 WT in heterologous cells reduced inward sodium current compared with NaV 1.5 WT alone or coexpressed with Kir2.1 WT . In cell surface biotinylation experiments, expression of Kir2.1 Δ314-315 reduced NaV 1.5 channel surface expression. Glycosylation analysis suggested that NaV 1.5 WT and Kir2.1 WT channels associate early in their biosynthetic pathway, and fluorescence recovery after photobleaching experiments demonstrated that coexpression with Kir2.1 increased cytoplasmic mobility of NaV 1.5 WT, and vice versa, whereas coexpression with Kir2.1 Δ314-315 reduced mobility of both channels. Viral gene transfer of Kir2.1 Δ314-315 in adult rat ventricular myocytes and human induced pluripotent stem cell–derived cardiomyocytes reduced inward rectifier potassium current and inward sodium current, maximum diastolic potential and action potential depolarization rate, and increased action potential duration. On immunostaining, the AP1 (adaptor protein complex 1) colocalized with NaV 1.5 WT and Kir2.1 WT within areas corresponding to t-tubules and intercalated discs. Like Kir2.1 WT, NaV 1.5 WT coimmunoprecipitated with AP1. Site-directed mutagenesis revealed that NaV 1.5 WT channels interact with AP1 through the NaV 1.5 Y1810 residue, suggesting that, like for Kir2.1 WT, AP1 can mark NaV 1.5 channels for incorporation into clathrin-coated vesicles at the trans -Golgi. Silencing the AP1 υ-adaptin subunit in human induced pluripotent stem cell–derived cardiomyocytes reduced inward rectifier potassium current, inward sodium current, and maximum diastolic potential and impaired rate-dependent action potential duration adaptation. Conclusions: : The NaV 1.5-Kir2.1 macromolecular complex pre-assembles early in the forward trafficking pathway. Therefore, disruption of Kir2.1 trafficking in cardiomyocytes affects trafficking of NaV 1.5, which may have important implications in the mechanisms of arrhythmias in inheritable cardiac diseases. Abstract : Supplemental Digital Content is available in the text.